2022
DOI: 10.1111/azo.12437
|View full text |Cite
|
Sign up to set email alerts
|

Integrated morphometric and molecular analyses indicate three male morphotypes in the freshwater prawn Macrobrachium olfersii (Decapoda, Palaemonidae) along the Brazilian neotropical region

Abstract: Males of Macrobrachium olfersii have a large cheliped (second pereiopod) with individual variations in shape and ornamentation, and they vary in size within and between populations. Some misidentification or doubts about taxonomic validity occur due to this morphological variability throughout their geographic distribution. We carried out a morphometric analysis to detect specific patterns and the potential occurrence of morphotypes in M. olfersii from different populations. Our data set included 52 females an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…This finding is consistent with other studies (Berglund, 1981; Boschi, 1974; Cartaxana, 2003; Kim, 2005; Koshy, 1969) that reported males of the palaemonid species are generally larger, with a highly evident sexual dimorphism. Several other studies reported this size predominant is frequently observed in species of Macrobrachium Spence Bate, 1868, mainly being associated with size and form of the chelipeds of adult males (Boschi, 1974; Nogueira et al, 2023; Nogueira, Mossolin, et al, 2022; Rossi et al, 2022; Santos et al, 2022). Bauer et al (2014) reported that, for many caridean species, males are significantly larger than females for ‘temporary mate guarding’ or ‘neighborhood of dominance’ mating systems, and that they use hypertrophied weapons (major chelipeds, third maxillipeds) to fight for and defend females.…”
Section: Discussionmentioning
confidence: 90%
“…This finding is consistent with other studies (Berglund, 1981; Boschi, 1974; Cartaxana, 2003; Kim, 2005; Koshy, 1969) that reported males of the palaemonid species are generally larger, with a highly evident sexual dimorphism. Several other studies reported this size predominant is frequently observed in species of Macrobrachium Spence Bate, 1868, mainly being associated with size and form of the chelipeds of adult males (Boschi, 1974; Nogueira et al, 2023; Nogueira, Mossolin, et al, 2022; Rossi et al, 2022; Santos et al, 2022). Bauer et al (2014) reported that, for many caridean species, males are significantly larger than females for ‘temporary mate guarding’ or ‘neighborhood of dominance’ mating systems, and that they use hypertrophied weapons (major chelipeds, third maxillipeds) to fight for and defend females.…”
Section: Discussionmentioning
confidence: 90%
“…This could explain why the OBC males' bodies do not develop as much as in other larger morphotypes. The OBC is a special male individual, with a major cheliped more developed than the normal BC type [51].…”
Section: Morphological Diversity Of Chelipedsmentioning
confidence: 99%
“…The characteristics of each morphotype's chelipeds impart a distinct role in the population and the environment in which it lives. The differential pattern in cheliped size, color, and spination certainly has an impact on the intraspecific interactions as well as the male's interaction with the environment [5,51]. The use of spines to differentiate male morphotypes is common in Macrobrachium species [5,10], as well as in other genera, such as Rhynchocinetes [45,46].…”
Section: Morphological Diversity Of Chelipedsmentioning
confidence: 99%